Antarctic Bioconstructional Bryozoans from Terra Nova Bay (Ross Sea): Morphology, Skeletal Structures and Biomineralization - Lombardi, Chiara; Kuklinski, Piotr; Spirandelli, Edoardo; Bruzzone, Giorgio; Raiteri, Giancarlo; Bordone, Andrea; Mazzoli, Claudio; López Correa, Matthias; van Geldern, Robert; Plasseraud, Laurent; Thomas, Jérôme; Marin, Frederic (Minerals, 2023)
Among Antarctic bryozoans, some species are able to develop calcitic bioconstructions promoting habitat complexity, but the processes leading to biomineral formation are mostly unknown. The present work investigated three Antarctic bryozoans, from morphological to skeletal features, including the organic matrix associated with the skeleton (SOM). Cellarinella nutti Rogick, 1956 and Reteporella frigida Waters, 1904 were collected in November 2018 from a shallow site (25 m) and Cellarinella njegovanae Rogick, 1956 from a deep site (110 m) at Terra Nova Bay (Ross Sea, Antarctica). Both Cellarinella species showed 5–6 “growth check lines” (gcl) on their laminae. The morphometrical characterization conducted on the growth bands (gb) and zooids, within the band across bands, revealed a variability in length with time (C. nutti: from 4099 µm for gb1 to 1449 µm for gb6; C. njegovanae: from 1974 µm for gb 3 to 7127 µm for gb2). Zooid length varied within gb, from the proximal to the distal part of the bands, but differences also occurred across bands. The shortest zooids ( 625 µm) were found at the proximal part and the longest ( 1190 µm) in the middle part of the gb in C. nutti, whereas in C. njegovanae the shortest zooids ( 660 µm) were found in the distal part and the longest ( 1190 µm) in the proximal part of the gb. Micro-CT analyses indicated the ratio of basal zooidal walls (RbwT gcl/gb) ranged from 3.0 to 4.9 in C. nutti and from 2.3 to 5.9 in C. njegovanae, whereas Reteporella frigida did not form any gcl on either side of the colony. Preliminary characterizations of the SOM for the three species evidenced a mixture of proteins and polysaccharides with properties similar to those of better-known biominerals, in terms of quantity and electrophoretic behavior. In addition, a “lectin fingerprint” has been established for the first time in bryozoans, displaying the presence of chitin or chitin-related saccharides. Understanding the complexity of the processes regulating skeleton formation is a key aspect in comprehending the adaptation of bioconstructional ecosystems and the survival of the associated biodiversity under the future ocean
Keywords: Bryozoa; Antarctica; calcifying ecosystem; growth check lines; zooid morphometrics; skeletal organic matrix (SOM); seawater stable isotopes; climate change